Special educational needs provision and academic outcomes for children with teacher reported language difficulties at school entry - Sarah Griffiths; Laura Lucas; Debbie Gooch; Courtenay Frazier Norbury (JCPP Advances)
Abstract Background Language ability predicts academic attainment across the curriculum. Teacher report of language difficulties may therefore help schools identify children that require Special Educational Needs (SEN) provision. Special Educational Needs provision is intended to enable children to reach their academic potential, however the effectiveness of this for children with language difficulties is unknown. Methods We linked teacher‐ratings on a brief language difficulties questionnaire (13‐item) collected in the first year of primary school (N = 7013), with data on SEN provision until age 12–13 and scores on statutory assessments at ages 5–6, 6–7 and 10–11 years from the National Pupil Database (UK). We conducted a preregistered analysis to (a) test the association between teacher‐reported language difficulties and later academic outcomes, (b) identify predictors of subsequent SEN provision for monolingual children with language difficulties and (c) test whether SEN provision is associated with better academic outcomes for these children. Results Teacher‐reported language difficulties predicted achievement in phonics (rs > 0.41), reading (rs > 0.38), writing (rs > 0.32) and maths (rs > 0.40) assessments up to 7 years later. For those with language difficulties, having an existing diagnosis of a neurodevelopmental condition or sensory impairment was the strongest predictor of SEN registration (OR [95% CI] 8.33 [4.12, 19.24]) and special education placement (OR [95% CI] 18.89 [9.29, 42.01]) during primary school. However, 38% of children registered as having a primary speech, language and communication need, lost this registration during transition to secondary education. We could not estimate the effect of SEN provision on academic outcomes, as the majority of children with high propensity to receive SEN provision did receive provision, and very few children in SEN settings completed statutory assessments. Conclusions Teacher perceptions of language difficulties at school entry, in the presence of additional risk factors, should prompt SEN provision. Recognition and support for language difficulties should be sustained throughout children's education.